Cephalometric Antero-Posterior Parameter Evaluation in Orthodontic Patients with Facial Asymmetries - Szuhanek, C; Nagib, R; Sabo-Meze, A; Buzatu, R; Malita, D (Journal of Dentistry And Oral Implants, 2020)
Aesthetic and functional problems associated with significant facial asymmetry can negatively affect the patient's facial appearance, nutritional and psychosocial development. Therefore, a critical assessment and accurate treatment planning is absolutely necessary. The aim of this study was to evaluate the parameters of PA cephalometric analysis defined by Ricketts and Grummons and establish statistically relevant correlations and their importance in diagnosing orthodontic patients with varying degrees facial asymmetries. The research included facial asymmetry Romanian patients from the Department of Orthodontics and Dento-Facial Orthopedics of UMF "Victor Babes", Timisoara. The PA cephalogram investigations that met the inclusion criteria were digitally analyzed. Dental and skeletal cephalometric parameters described by Ricketts, Grummons and Kappeyne Van De Coppello were collected through linear, angular and volumetric measurements. Statistically significant correlations between the degree of asymmetry and the dimension of the internal structures were observed.Our conclusion is that PAcephalograms are cost effective and useful investigations in identifying and evaluating skeletal and dental imbalances in orthodontic facial asymmetry patients.
Keywords: Facial asymmetries; orthodontic patients; skeletal cephalometric parameters